P53 and Nuclear Unrest: Biological Driver’s Suggesting Poor Prognosis in Anaplastic Wilm’s Tumor - Agarwal, Kiran; Anand, Amrita (Journal of Pediatric Nephrology, 2020)
In the early era, survival from Wilm’s tumor (WT) was less than 10% compare to today's date which has a 90% chance of survival. Multimodal therapy, enhanced surgical techniques, effective chemotherapy regimens and radiation therapy in treatment protocols have revolutionized the survival rates. As the advancement continues, molecular basis and targeted therapies are being considered for risk stratification and better treatment. Particularly important is evaluation of molecular abnormalities that confer to poor prognosis, so that intensification of chemotherapy and radiotherapy can be done to achieve maximum remission. The aim of this article is to highlight the importance of p53 and a morphological spectrum that have been associated with prognosis in WT.